The effect of intracerebral structure volumes on idiopathic intracranial hypertension. Issue 1 (6th January 2021) - Ozkal, Birol; Ozen, Ozkan
Abstract : Background: This aim of this study was to assess the effect of idiopathic intracranial hypertension (IIH) in the development of intracranial hypertension by measuring patients' cerebrospinal fluid (CSF), brain, and segment volumes. IIH is a disease of unknown cause characterized by chronic CSF pressure elevation and papillary edema. Under the Monro–Kellie doctrine, efforts have been made to explain the disease through an increase in the volumes of one or two of brain, blood or CSF in the intracranial cavity, although these have not been completely successful. Methods: Twelve IIH patients diagnosed based on the modified Dandy criteria and 15 age- and sex-compatible healthy controls were included in the study. Cases' 3D T1 sequence images were evaluated using the voxel-based volumetric analysis system (volBrain). Intracranial cavity extraction, macrostructures, and subcortical structure volumes were measured and compared. Results: No statistically significant differences were observed between control cases' and IIH patients' CSF, cerebrum, cerebellum, brainstem, and subcortical structure volumes. Conclusion: IIH arises from a chronic cause that does not impair the volumetric balance between structures inside the intracerebral cavity.